The predictive value of MUC5AC levels in the sputum of children with Mycoplasma pneumoniae pneumonia treated with fiberbronchoscopy - Xiao-qing Jian; Miao Li; Xiao-yan Wang (Microbiology Spectrum)
ABSTRACT To investigate the predictive value of mucin 5AC (MUC5AC) levels in the sputum of children with Mycoplasma pneumoniae pneumonia (MPP) treated with fiberbronchoscopy. Children with lobar MPP who were hospitalized in the pediatric pulmonary department of Shengjing Hospital of China Medical University from October 2022 to September 2023 were enrolled. The expression of MUC5AC in sputum was detected by enzyme-linked immunosorbent assay (ELISA). Fiberbronchoalveolar lavage fluid (BALF) was collected, and MUC5AC and epidermal growth factor (EGF) levels in BALF were detected by ELISA, followed by retrospective analysis of the clinical and laboratory test data from each group. The risk factors for fiberbronchoscopy treatment in children with lobar MPP were analyzed by multivariate logistic regression, a nomogram model created, and a receiver operating characteristic curve drawn. Multivariate logistic regression analysis revealed that increased MUC5AC in sputum, lactate dehydrogenase (LDH), IgM levels in serum, and neutrophil-to-lymphocyte ratio (NLR) were risk factors for requiring fiberbronchoscopy treatment in children with lobar MPP (P < 0.05); the MUC5AC level in sputum had the highest predictive value (AUC = 0.806). The level of MUC5AC in sputum positively correlated with the levels of LDH, C-reactive protein (CRP), D-dimer, and NLR in serum, and the level of MUC5AC in sputum correlated with the levels of MUC5AC and EGF in BALF in each group. Increased sputum MUC5AC levels, and serum LDH, IgM, and NLR in children with lobar MPP are risk factors for requiring fiberbronchoscopy treatment, and sputum MUC5AC level has superior predictive value to predict the necessity of fiberbronchoscopy treatment to remove a mucus plug.IMPORTANCEMycoplasma pneumoniae is a common pathogen of pneumonia in children, and some severely affected children are accompanied by mucus plugs. The level of MUC5AC has important predictive value for mucus hypersecretion. To develop a means of predicting airway mucus secretion in children as early as possible when fiberbronchoscopy could be used to clear airway mucus plugs and reduce sequelae, this article analyzed the risk factors for fiberbronchoscopy treatment in children with lobar M. pneumoniae pneumonia (MPP). We identified that the level of MUC5AC in sputum positively correlated with the levels of Lactate dehydrogenase (LDH), C-reactive protein (CRP), D-dimer, and neutrophil-to-lymphocyte ratio (NLR) in serum and the levels of MUC5AC and EGF in BALF of the children with lobar MPP. Increased sputum MUC5AC levels, and serum LDH, IgM, and NLR in children with lobar MPP are risk factors for requiring fiberbronchoscopy treatment, and sputum MUC5AC level has superior predictive value to predict the necessity of fiberbronchoscopy treatment to remove a mucus plug.